Allelic Variation in Zmfatb Gene Defines Variability for Fatty Acids Composition Among Diverse Maize Genotypes - Katral, Ashvinkumar; Muthusamy, Vignesh; Zunjare, Rajkumar U.; Chhabra, Rashmi; Maman, Shalma; Yadava, Devendra K.; Hossain, Firoz (Frontiers in Nutrition, 2022)
Edible oil with lower saturated fatty acids is desired for perceived quality and health benefits to human and livestock. fatb gene encoding acyl-ACP thioesterase is a key player in conversion of palmitic acid to oleic acid, thereby modifying the ratio of saturated to unsaturated fatty acids in maize kernels. The present investigation characterized the full-length sequence of Zmfatb gene (4.63 kb) in two mutant (Zmfatb) and eight wild-type (ZmfatB) inbreds to study allelic variation, gene-based diversity, phylogenetic-relationship, protein-modelling and molecular-docking to identify novel candidates for modification of fatty acid profile. Sequence-alignment revealed wide genomic variability for Zmfatb among the inbreds; and identified five novel SNPs and two InDels that clearly differentiated the wild-type and mutant genotypes. Gene-based diversity using 11-InDel markers categorized 48-diverse maize-inbreds into two-clusters. Majority of mutant and wild type inbreds were grouped in separate clusters and led to generation of 41 haplotypes. Genetic-relationship of maize fatb gene with orthologues among 40 accessions of 12 oilseed-crops using both nucleotide and protein sequence clustered maize, soybean, sunflower, opium-poppy, Citrulus lanata, quinoa and prunus species into one cluster; and brassica, camelina and arabidopsis into different cluster. Clustering pattern revealed that the plant oil with higher unsaturated fatty acids, particularly oleic, linoleic and linolenic acids grouped together in one cluster and higher proportions of other fractions like arachidic, eicosenoic and erucic acids grouped in another cluster. Physico-chemical properties highlighted more similarity between maize and 29 orthologue proteins, but orthologues were found to have better thermostability. Homology models have been developed for maize mutant and wild-type inbreds using Umbellularia californica (PDB ID: 5x04) as template. Predicted protein models possessed optimum confidence-score and RMSD values and validated stability via., Ramachandran plots. Molecular docking indicated most of the interactions of protein-ligand were having similar binding-affinity due to broader specificity of fatty acyl-ACP thioesterases and presence of conserved-domains across crops. This is the first report on comprehensive molecular characterization of fatb gene in maize and various orthologues. The information generated here provided new insights into the genetic diversity of fatb gene which can be utilized for enhanced nutritive value of oil in the breeding programme.